Communication and Coordination Strengthening The Synergy of Cross-Border Traffic of Foreigners at The Entikong Border, West Kalimantan - Wuysang, Julia Magdalena; Alunaza, Hardi; Pijoh, Feibe Engeline (Technium Social Sciences Journal, 2024)
The cross-border traffic of foreigners in Entikong increased when the land border between Indonesia and Malaysia was opened in April 2022. The surge in activity has forced local governments to work together to ensure that monitoring runs well. The geographical condition of Entikong, which is dominated by forests and local plantations, also allows for the movement of foreigners outside official routes. Therefore, cooperation between government agencies and security forces is needed. Immigration then became one of the agencies that played an important role in supervising foreign nationals (WNA). This agency has a special board that monitors and analyzes every foreigner who enters Indonesian territory. Through a qualitative descriptive approach and data collection techniques from interviews, this research aims to observe the synergy and work system between Entikong regional government agencies carrying out supervision. The research is divided into three discussions, namely monitoring the cross-border traffic of foreigners based on Immigration Law at the Entikong border, control and supervision of foreigners by the PORA Team (Foreigner Surveillance Team) of Entikong Immigration Office, and synergy in monitoring the cross-border traffic of foreigners in the EntikongPLBN work environment. The final results of the research show that the PORA Team of Immigration Office Class II Entikong is trying to strengthen the synergy between its members so that coordination in conveying information can run smoothly and cases of violations will decrease. However, increased intensity is needed in monitoring cross-border traffic of foreigners in joint operations.